Temporal Aspects of Crime Events: Conceptual Approaches in Expert Analysis - Elena A. Logvinets; Natalya P. Katorgina (RUDN Journal of Law)
The problem of establishing the temporal characteristics of a crime event has been a subject of study in expert practice for over thirty years. Despite this, law enforcement and researchers have yet to reach a consensus on the relationship between various categories used to describe the time course of a crime. Experts employ terms such as “remoteness”, “duration”, “chronology”, “period”, “age”, and “length” to characterize crime events in terms of time. However, these concepts are used inconsistently: some researchers treat them as equivalent, others differentiate them by their content, and still others use mutually exclusive terms. This inconsistency stems from the lack of a unified conceptual and categorical framework in this field. Therefore, developing modern approaches, and refining existing ones, for understanding the temporal characteristics of crime events used in establishing temporary information is both justified and necessary. This research examines various concepts of time and analyzes theoretical approaches to understanding the nature of time in law enforcement. Particular attention is given to the consideration and correlation of similar categories used in expert practice to establish temporal characteristics. The results were obtained using a range of research methods, including historical analysis, comparative legal analysis, synthesis, and deduction. These methods contribute to the study’s primary goal: to systematize and develop a system of categories that reflects various temporal characteristics of a crime event. The findings of this study may determine the development of a unified approach to using categories that describe the temporal characteristics of crime events in court proceedings.